The Influence of Price and Quality Product on Purchase Intention of Toyota Agya in Tuban City - Istiqomah, Nur Hidayatul; Fauzi, M. Risky; Faizah, Filla Nor (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of price and product quality on consumer purchase intention toward Toyota Agya vehicles in Tuban City. Purchase intention plays a crucial role in determining consumer decision-making and serves as an important indicator for companies in formulating effective marketing strategies. The declining sales performance of Toyota Agya, despite its position as one of the top city car brands in Indonesia, highlights the need to examine the factors influencing consumer interest in purchasing this product. This research employs a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to prospective buyers and consumers who have purchased or intend to purchase Toyota Agya cars in Tuban City. A purposive sampling technique was applied, resulting in a total sample of 110 respondents. The data were analyzed using statistical methods with the assistance of SPSS version 26, including validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that price has a positive and significant effect on consumer purchase intention. Similarly, product quality also has a positive and significant effect on purchase intention. Furthermore, the simultaneous testing results show that price and product quality jointly have a positive and significant influence on consumer purchase intention toward Toyota Agya vehicles. Although the coefficient of determination indicates that the explanatory power of the model is relatively limited, the findings confirm the importance of aligning price and product quality with consumer expectations.